An ultrasonic visualization system using a fiber-optic Bragg grating sensor and its application to damage detection at a temperature of 1000 °C. (15th January 2021) - Yu, Fengming; Saito, Osamu; Okabe, Yoji
Highlights: We propose a novel laser ultrasonic visualization technique using an optical fiber sensor. The developed system can visualize the propagation of Lamb wave at 1000 °C temperature. Wavenumber-frequency analysis is applicable to the visualized results at the elevated temperature. Damage detection is realized by means of the system under the high-temperature environment. Abstract: Structural health monitoring (SHM) techniques are required to evaluate the reliability of aging heat-resistant structures. To build a method of high-temperature in situ damage diagnosis, the authors developed a laser ultrasonic visualization system with a heat-resistant fiber-optic Bragg grating (FBG) sensing configuration. In this system, an ultrasonic wave is excited by laser irradiation on the surface of a material and then received by a remotely installed FBG sensor. Because both the wave excitation and wave sensing parts have excellent heat resistance, the proposed sensing system enables a stable ultrasonic measurement at a temperature of 1000 °C. In this research, a wavenumber-frequency analysis shows that the proposed sensing system was able to visualize the correct laser ultrasonic wavefield in a planar structure. The ultrasonic visualization performance was then verified for a plate of heat-resistant material at temperatures of 200 and 1000 °C. A wavenumber-frequency analysis based on a three-dimensional Fourier transform was also conducted to extract the wave components corresponding to the reflection caused by an artificial defect in the plate. As a result, the developed method enabled clear damage identification at temperatures as high as 1000 °C.